Assessment of the Heterotrophic Bacterial Contamination in Waterlines of Dental Units as a Potential Health Risk Factor in Occupational and Patient’s Exposures - Ali Shahryari; Amineh Zahed; Abdolhalim Rajabi; Maryam Shafipour; Niloufar Emrani; Hadi Rahimzadeh; Hamidreza Heidari (Journal of Health Sciences and Surveillance System)
Background: Waterlines in dental units can harbor various types of bacteria and microorganisms, including heterotrophic bacteria, which can pose a health risk to patients and dental personnel. This study aimed to investigate the extent of heterotrophic bacterial contamination in the waterlines of dental units and evaluate its potential as a health risk factor for occupational and patient exposure.Methods: This cross-sectional study selected four active departments at the Faculty of Dentistry, Golestan University of Medical Sciences (Gorgan, Iran). Bacterial contamination in the waterlines, dental handpieces, and other water-related components of dental units was investigated and analyzed in terms of Colony-Forming Units per milliliter (CFU/ml). The data were analyzed using the Kruskal-Wallis and Wilcoxon signedrank tests using SPSS version 23.Results: The mean and standard deviation of bacterial contamination across all studied departments were significantly higher than the recommended limit of 500 CFU/ml (ranging from 10,250.00±8,924.28 CFU/ml for the inlet to the water tank in the pediatric department to 275,625.00±41,520.86 CFU/ml for the air-water syringe before flushing in the surgery department). No significant differences were observed between departments (P>0.05). Furthermore, there were no significant differences in bacterial contamination between different days and hours of sampling (P>0.05), although bacterial levels were higher on Saturdays and mornings. Flushing the waterlines for 30 seconds reduced bacterial contamination (P<0.05).Conclusion: Stagnation of water in dental unit waterlines, particularly over weekends or after working hours, using reserve water during dental procedures, and insufficient flushing of dental handpieces resulted in consistently high bacterial contamination levels. Therefore, using fresh water and performing proper flushing in dental handpieces is strongly recommended to mitigate the risks associated with bacterial contamination.